Odyssey Self Reflection - Souvenir collection / Faculty of Art and Design UiTM Cawangan Sarawak - Mohd Rathi, Mohd Razif
My idea originated from the experience of traveling with my family. The experience then inspired me to create artworks which comprised of drawing, painting, printmaking and sculpture. I conceptualised my artwork according to the notion of preserving memories through the act of collecting souvenirs. The elements and principles infused in the artworks were warm and cool colours, value, the form of key chains and asymmetrical division between two images. I used mixed techniques for drawing artwork, specifically charcoal and soft pastel.